SkinCancerNet: Automated Classification of Skin Lesion Using Deep Transfer Learning Method - Tasar, Beyda (Int Information & Engineering Technology Assoc, 2023)
Skin cancer has become one of the most common diseases due to the depletion of the ozone layer and the decrease in its protection. Detection and classification of skin cancer in the early stages of its development allows patients to receive appropriate treatment quickly. In this article, a modified CNN framework based on transfer learning is proposed for the classification of skin lesions from skin dermoscopy images. In the proposed framework, pre -trained CNN architectures are used. VGG16, ResNet50, DeneNet121, MobileNet, and Xception models were pre-trained using ImageNet images and training weights. In the study training and tests were performed on the HAM10000 skin lesions data set. The classification accuracy of the modified DenseNet121, VGGNet16, ResNet50, MobileNet, and Xception models were calculated as 94.29%, 93.28%, 87.10%, 83.10%, and 80.05% respectively. It was observed that the accuracy success of the proposed transfer learning framework in skin lesion type classification surpasses classical deep learning architectures.
Keywords: transfer learning deep learning skin; cancer skin lesions